The conclusion sections in applied linguistics international journal articles written by Indonesian authors - Alkamillah, Muhammad; Azwandi, Azwandi; Maisarah, Ira (Journal of Applied Studies in Language, 2022)
This research attempts to describe the rhetorical structures of Indonesian author's in the conclusion section of applied linguistics international journals articles. The method employed in this study is descriptive quantitative. Thirty RA conclusion sections were extracted from two international journals; the Indonesian Journal of Applied Linguistics (IJAL) and TEFLIN journal, and examined based on the rhetorical move following Yang & Allison's proposed model of conclusion section (2003). The result revealed that, first,  the majority of RA Conclusion sections (22 [73%] out of 30 conclusion sections) contain all elements of the Conclusion sections outlined by Yang and Allison (2003), namely:  obligatory; move 1 (summarizing the study), the conventional moves; move 2 (Evaluating the study) and move 3 (deduction from the research); second, concerning steps features, most Indonesian authors tend to use step 1 in realizing move 2 (evaluating the study) This implies that those authors tend to justify their study by indicating the result of the research in evaluating the study in the conclusion section rather than stating the limitation of the research or evaluating the methodology in the conclusion section. In move 3, the Indonesian author tends to use step 1 (recommending future research) in realizing this move. This implies that the author prefers to state the possible areas for future study of study rather than drawing pedagogic implications. In conclusion, most Indonesian authors fulfilled the rhetorical structure of yang and Allison proposed model in their conclusion section.